2020
DOI: 10.3390/foods9060711
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Treatments of Cereals: Effects on Thermophysical and Parenchymal-Related Properties

Abstract: Dielectric heating is one of the most interesting techniques for pest disinfestation. However, most of the literature works give information about the ability of microwave treatments at different power-time conditions to kill insects; less is given about the analysis of matrices structural properties and heat transport. Accordingly, the aim of this work is to investigate the effect of microwave treatments, applied for pest disinfestation, on heat transport behavior and physical/structural properties, such as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…A similar trend for bulk and TD was reported by Rao et al (2021) in the case of MW treatment of foxtail millet flour. Barba et al (2022) reported a non‐significant change in BD and TD of durum wheat, weak wheat, and corn during MW treatment. The BD can be used in the design of packaging, to determine the flow property of flour in different food processing operations (Yadav et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend for bulk and TD was reported by Rao et al (2021) in the case of MW treatment of foxtail millet flour. Barba et al (2022) reported a non‐significant change in BD and TD of durum wheat, weak wheat, and corn during MW treatment. The BD can be used in the design of packaging, to determine the flow property of flour in different food processing operations (Yadav et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The high rate of mass transfer (moisture migration from herbs to the process environment) can cause tissue damage such as cracking events. To assay this, the evaluation of electrolyte loss is one method adopted as an indirect measure of cell wall integrity [ 32 , 33 , 34 , 35 ]. Tissue alterations of fruit and vegetables due to thermal or mechanical injuries for storage or treatment purposes (very low or high temperatures involved in freezing or in drying; washing and centrifugation) can result in an increase in the ions’ release rate from the vegetal structures in a dissolution medium [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hot-air drying (CD2) causes greater tissue damage with respect to the convective one under room conditions due to exposure to higher temperatures (50 °C). Microwave-assisted drying treatments, both at 2300 W and 1150 W (MDW1-MDW2: p > 0.05), cause the most intense damage to vegetal structures, as shown by the fast and high losses of electrolytes due to the peculiar action of heat and mass transfer phenomena previously described [ 9 , 34 , 35 ]. However, this result should not necessarily be seen as a negative effect.…”
Section: Resultsmentioning
confidence: 99%
“…One method for assessing tissue damage in herbs and other plant matrices is the assessment of electrolyte loss, which constitutes an indirect measure of cell wall integrity 27 29 .…”
Section: Resultsmentioning
confidence: 99%